EDUCATION OF LEGAL TRANSLATION: NEEDS, HORIZON, AND CHALLENGES IN PAKISTAN - Dr. Shair Ali Khan; Dr. Zainab Amin; Dr Samina Begum (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
New Pakistan needs a huge number of professional translators to be communicative agents in the global village meeting the needs of the gigantic economic project CPEC, all legal circles, diplomatic domains, and a large number of institutions along with the individual needs of people. In terms of professional legal translators, Pakistan faces a number of challenges to fill the gap in the domains of legal translations such as the utilization of legal translation tool, preparation of term banks, databases, bilingual and multilingual legal translation dictionaries, terminography of legal domains. On the other hand, the verdict of Supreme Court regarding induction of Urdu as the official language of correspondence in all the governmental, semi-governmental and other substitute organizations. So, this decision put all the institutions in a big challenge of finding and induction of huge number of professional translators in various domains such as law, medical, media, commerce, trade, economics, business, political circles and education. Hence, focusing on legal institutions, a huge number of translators are needed to be employed for the faithful transfer of legal decisions, legal texts, legal correspondence from Urdu to English and vice versa and other diplomatic languages. Therefore, looking to the dire need of professional translators in legal domains, it is the time to put translation as a subject in the educational institutions accepting the interdisciplinary nature of legal translation, and to carry out the serious text transfer activity. The International Islamic University of Pakistan Islamic has the credit of establishing a full department of Translation & Interpretation. Whereas, the law department has a big space for the education of Legal Translation. All these challenges, future horizons, and CPEC project justify the education of legal translations in the academic programs. Therefore, the study aims at finding out the areas, needs, and space for the education of legal translation keeping in view the broad translational challenges in New Pakistan.